2016
DOI: 10.7314/apjcp.2016.17.2.463
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Valproic Acid in Improving Radiation Therapy for Glioblastoma: a Review of Literature Focusing on Clinical Evidence

Abstract: Glioblastoma (GBM) is the most common and aggressive type of primary brain neoplasm. The current standard therapy for GBM consists of maximal surgical resection within safe limits, followed by radiation therapy (RT) and chemotherapy with temozolomide. Despite advances in treatment, the prognosis of GBM remains poor. Epileptic seizure is one of the most common symptoms in patients with GBM. Valproic acid (VPA), a histone deacetylase inhibitor, is often used as an anti-epileptic drug in patients with brain neopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 30 publications
0
11
0
1
Order By: Relevance
“…Several retrospective studies analyzed the effects of VPA on the survival of GBM patients [104106]. Although these results have suggested favorable effects of VPA, whether VPA improves the OS of GBM patients is debatable [107]. However, a phase II trial of VPA, temozolomide, and concurrent radiotherapy for GBM patients was investigated and promising results were recently reported [13].…”
Section: Clinical Trials Of Hdac Inhibitors In Gbmmentioning
confidence: 99%
See 1 more Smart Citation
“…Several retrospective studies analyzed the effects of VPA on the survival of GBM patients [104106]. Although these results have suggested favorable effects of VPA, whether VPA improves the OS of GBM patients is debatable [107]. However, a phase II trial of VPA, temozolomide, and concurrent radiotherapy for GBM patients was investigated and promising results were recently reported [13].…”
Section: Clinical Trials Of Hdac Inhibitors In Gbmmentioning
confidence: 99%
“…The most common grade III/IV toxicities of the combination regimen are metabolic and laboratory toxicities (8%), neurological toxicity (11%), and blood and bone marrow toxicity (32%) (NCT00302159) [107], which seem to be well tolerated. Based on the considerable preclinical and retrospective data, VPA is considered to be one of the most promising agents for GBM treatment, but prospective data are still limited [107]. Further investigations are needed to assess its efficacy and clarify the optimal treatment.…”
Section: Clinical Trials Of Hdac Inhibitors In Gbmmentioning
confidence: 99%
“…Subgroup analysis showed that patients treated with VPA had a HR of 0.74 (95% CI: 0.59‐0.94) vs patients treated with other antiepileptic drugs (AEDs) and a HR of 0.66 (95% CI: 0.52‐0.84) vs patients treated with non‐AEDs. The results of other retrospective studies have also indicated potential benefit of VPA in improving survival of patients with glioblastoma . Nevertheless, there are also reports suggesting that VPA may not be associated with any survival benefit in these patients.…”
Section: Resultsmentioning
confidence: 99%
“…The results of other retrospective studies have also indicated potential benefit of VPA in improving survival of patients with glioblastoma. 108 Nevertheless, there are also reports suggesting that VPA may not be associated with any survival benefit in these patients. One retrospective study in a cohort of 1263 patients with glioblastoma reported that none of the six AEDs, including VPA, prescribed for symptomatic epilepsy significantly altered OS.…”
Section: Potential Use In Oncologymentioning
confidence: 99%
“…Эпилептические припадки являются одним из наиболее распространенных симптомов у пациентов с ГМ. Появление, учащение приступов, серийное и статусное их течение часто наблюдаются после операции на фоне проведения ЛТ и ХТ [1,2].…”
Section: введение / Introductionunclassified